1998
DOI: 10.1177/03635465980260051301
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Collegiate Wrestling

Abstract: We evaluated the data of the National Collegiate Athletic Association Injury Surveillance System on collegiate wrestling with a focus on musculoskeletal injuries. Over 800,000 athlete-exposures during an 11-year period compose these data. Findings particular to wrestling and a comparison with other collegiate sports are included. Collegiate wrestling had a relatively high rate of injury at 9.6 injuries per 1000 athlete-exposures. It was second to spring football in total injury rate. Most injuries in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
110
3
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 8 publications
8
110
3
5
Order By: Relevance
“…The difficulty in the comparison of data among studies is due to the absence of an uniform standard in the classification of lesion types. 4 The types of lesion most frequently reported in our study were sprains (34.5%) and muscle lesions (30.4%), which is in line with the results presented by Jarrett et al 4 , Pasque et al 5 and Snook 6 . These authors said that contusions are the third most common lesion in wrestlers, unlike our data in which contusions were the least frequent lesions.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The difficulty in the comparison of data among studies is due to the absence of an uniform standard in the classification of lesion types. 4 The types of lesion most frequently reported in our study were sprains (34.5%) and muscle lesions (30.4%), which is in line with the results presented by Jarrett et al 4 , Pasque et al 5 and Snook 6 . These authors said that contusions are the third most common lesion in wrestlers, unlike our data in which contusions were the least frequent lesions.…”
Section: Discussionsupporting
confidence: 92%
“…Several anatomical regions are injured as a result of the practice of wrestling. 4,11 We found that the topography with the highest number of lesions was the knee (25.5%), followed by the shoulder (20%), which is consistent with the findings of most researchers.1,4,6,12,13 Only Pasque and Hewett5, in a prospective study with adolescent athletes for a season, found a Average length of absence due to injury 2.1 (0.5 -9) months…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations